Modern approaches to the examination of patients with anorexia nervosa - Sak, Леся (Psychosomatic Medicine and General Practice, 2020)
Objective. Eating disorders (EDs) are mental disorders characterized by specific brain dysfunctions that affect bodily perception, the relationship of emotions and appetite, cognitive impairment. Modern treatments for EDs are still imperfect, particularly for anorexia nervosa (AN). AN has low remission rates and high recurrence rates. Psychopathological models of AN, which are the basis of global protocols for the treatment of AN, are still far from explaining the causal relationships that underlie resistance to treatment. Modern models of AN, as a rule, focus on the cognitive and behavioral characteristics of patients, without explaining the important etiological factors underlying emotional dysregulation, impaired interpersonal functioning, the concept of "I" and mentality, which play an important role in developing and maintaining AN. AN occurs among different age groups, but the average age of onset is most common in adolescence. Recent studies have demonstrated a significant association between AN and parental psychopathological risks in addition to the importance of family functioning and attachment. Most of these studies have focused on the relationship between the presence of psychopathological disorders in the mother and psychopathological risks and/or the development of AN, not taking into account the likely influence of other family members involved in the upbringing of the child/adolescent. Thus, AN is a severe psychosocial disorder involving the patient and his family; that is why the problem of a comprehensive examination of the patient AN and members of his family (parents/guardians) is relevant worldwide. Aim. The aim of the study was scientific substantiation and improvement of medical and psychological support of patients with AN in the context of family relations based on the study of clinical and psychopathological, pathopsychological characteristics of people with AN and their parents/guardians, indicators of family functioning, and quality of social support. Methods and materials. To conduct a study of patients with AN and their parents/guardians in the context of family relationships who first sought medical care, with further improvement of medical and psychological support of these contingents, based on qualitative and quantitative content analysis and conceptual analysis using meta- analyzes and systematic reviews of the scientific literature on the study of the problem of AN, the optimal battery of psychodiagnostic scales with their approbation within the pilot study was determined and selected. Results. To verify the adequacy of the tests, a pilot study was conducted on 12 patients (11 girls, 1 boy) aged 14-18 years and 20 parents/guardians (12 persons - mothers, 4 persons - fathers, 2 persons - stepfathers, 2 persons - grandmothers). The study consisted of the following methods: Mini-mental State Examination (MMSE), Minnesota Multiphasic Personality Inventory (MMPI), Family Adaptation and Cohesion Scale (FACES-III), Emotional Difficulty Scale (Gratz & Roemer 2004), Toronto Alexithymia Scale, Adult Attachment Interview (AAI), Hospital Anxiety and Depression Scale (HADS). Quality of Life Assessment Scale (CQLS). The pilot study found that most psychodiagnostic techniques provide a detailed description of family functioning and psychoemotional status of patients with NA and their parents/guardians, which allows assessing the effectiveness of the developed program of psychocorrection and prognostic value of psychoemotional changes. Conclusions. The results of our study allow us to determine with sufficient probability the relationship between the occurrence of AN and the peculiarity of family functioning and the psycho-emotional status of parents or guardians. The selected set of research methods has confirmed its effectiveness, which makes it possible to extend it to the entire planned contingent of dissertation research participants.